Program Halo BK: Solusi Pelayanan Bimbingan dan Konseling Dimasa Pandemi Covid-19 - Khasanah, Lailatul Nurul; Hariastuti, Retno Tri; Darminto, Eko (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
The Halo BK program is an online or online-based guidance and counseling service activity that is packaged in the VOS Podcast discussion technique by utilizing Youtube TV, VOS radio, and VOS TV media. The Halo BK program provides various information and assistance on personal, social, learning, and career aspects and helps students identify themselves (self-concept), get to know the environment, and plan for the future. The research method uses qualitative research, with the type of literature study. The objectives of the Halo BK program are: (1) Helping students gain an understanding of the information provided, (2) Helping students use the information to help solve problems, (3) Helping students become more independent, (4) Helping students to think positive and objective in adapting to their environment, (5) Helping students to be able to make decisions, (6) Helping students being able to direct themselves according to their needs (7) Helping students being able to actualize themselves.